2020
DOI: 10.3389/fnmol.2020.554547
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 4 Affects Epilepsy by Regulating Glial Cells: Potential and Possible Mechanism

Abstract: Epilepsy is a chronic brain dysfunction induced by an abnormal neuronal discharge that is caused by complicated psychopathologies. Recently, accumulating studies have revealed a close relationship between inflammation and epilepsy. Specifically, microglia and astrocytes are important inflammatory cells in the central nervous system (CNS) that have been proven to be related to the pathogenesis and development of epilepsy. Additionally, interleukin 4 (IL-4) is an anti-inflammatory factor that can regulate microg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 91 publications
0
7
0
1
Order By: Relevance
“…This increase in IL-4 appeared more robust in the cortex, particularly within the sham injured groups. The cytokine, IL-4, is well known to promote anti-inflammatory phenotypes in microglia and astrocytes [ 50 , 51 ]. Upon treatment with IL-4, macrophages [ 52 ] and microglia [ 53 , 54 ] polarize to a more anti-inflammatory phenotype associated with increased expression of anti-inflammatory cytokines such as Ym1, Fizzl, and IL-10.…”
Section: Discussionmentioning
confidence: 99%
“…This increase in IL-4 appeared more robust in the cortex, particularly within the sham injured groups. The cytokine, IL-4, is well known to promote anti-inflammatory phenotypes in microglia and astrocytes [ 50 , 51 ]. Upon treatment with IL-4, macrophages [ 52 ] and microglia [ 53 , 54 ] polarize to a more anti-inflammatory phenotype associated with increased expression of anti-inflammatory cytokines such as Ym1, Fizzl, and IL-10.…”
Section: Discussionmentioning
confidence: 99%
“…Silverberg et al found in mice study that a single tonic-clonic seizure induces IL-4and IgE-negative T and B cells to migrate to the brain and transform into Il-4+ and IgE+ cells, respectively [49]. There is an increase in Il-4 in the serum of patients after seizures, indicating that this cytokine may be a natural response of the body to injury [50,51]. Nevertheless, it is worth mentioning that, due to the multimodal action of cytokines, IL-4 can play anti-inflammatory or pro-inflammatory roles in different environments [50,51].…”
Section: Epilepsymentioning
confidence: 99%
“…There is an increase in Il-4 in the serum of patients after seizures, indicating that this cytokine may be a natural response of the body to injury [50,51]. Nevertheless, it is worth mentioning that, due to the multimodal action of cytokines, IL-4 can play anti-inflammatory or pro-inflammatory roles in different environments [50,51]. IL-4 therefore likely plays a significant role in epileptogenesis and the physiopathology of epilepsy [50,51].…”
Section: Epilepsymentioning
confidence: 99%
See 1 more Smart Citation
“…По своей иммунологической роли является сильным противовоспалительным цитокином, способным угнетать выработку макрофагами воспалительных цитокинов, таких как ИЛ-1, -6, фактор некроза опухолей (ФНО), а также обеспечивать сильный противоопухолевый иммунитет [43]. Способность снижать уровни воспалительных цитокинов, обладающих сильным возбуждающим действием на нейрон, делает ИЛ-4 потенциальным противосудорожным агентом [25]. Тема о влиянии ИЛ-4 все еще нова, так как первая экспериментальная работа на эту тему была опубликована в 2017 г. На крысах с искусственно смоделированной эпилепсией исследователи продемонстрировали способность ИЛ-4 не только уменьшать клинические проявления эпилепсии, но и влиять на состояние микроглии [37].…”
Section: интерлейкин-4unclassified